Collaboration uncovered : the forgotten, the assumed, and the unexamined in collaborative education - Richards, Merle, 1941- (Bergin & Garvey, 2001)
Annotation Researchers and teachers must work together to improve education by establishing strong collaborative connections so that theory and practice can inform one another. In addition to describing and discussing benefits and positive examples, the articles explore examples of negative collaborative relationships and raise a number of issues, such as the role of negotiation in collaborative projects, that can serve to inform readers' subsequent experiences with collaborative initiatives.